DEVELOPMENT OF STUDENTS' INTERESTS IN THE FIELD OF HUMANITIES EDUCATION (Spectrum Journal of Innovation, Reforms and Development, 2022)
In modern social conditions, it is of particular relevance  the problem of the formation of general cultural competencies and its important component - social and humanitarian competence as an integral quality of training  specialists for professional activities in the legal field.